Advances in research on the use of Brevundimonas spp. to improve crop and soil fertility and for soil bioremediation - Souad, Zaim; Ahmed Amine, Bekkar (Université of Eloued-جامعة الوادي, 2023)
Biofertilizers or biological fertilizers maintain soil fertility by fixing atmospheric nitrogen, solubilizing P and K, producing plant growth substances and antibiotics as well as biodegradation of organic matter in the soil that enriches the root rhizosphere. Microbial biofertilizers are eco-friendly and less expensive alternatives to chemical fertilizers. The key components of healthy soil are populations of plant growth promoting rhizobacteria (PGPR) which play multiple beneficial and ecological roles in the rhizosphere soil. PGPR colonizes rhizosphere or plant roots, resulting in phytostimulation, biofertilization and biocontrol either directly and/or indirectly. Another important role of PGPR is its ability to decontaminate soils through a process called soil bioremediation. Recently, the known rhizobacteria environmentally friendly biofertilizers for sustainable agriculture are those belonging to Brevundimonas spp., which play a significant role in improving crop production and soil health .
Keywords: biofertilizer, PGPR, Brevundimonas spp., crop production, soil health, Agriculture.